PERLINDUNGAN HUKUM HAK CIPTA ATAS FILM LAYAR LEBAR YANG DIPUBLIKASI MELALUI MEDIA SOSIAL TANPA IZIN - Nurkhaliq Khussamad Noor (Faculty of Law, Universitas Riau, 2019)
In Law Number 28 of 2014 concerning Copyright it is regulated that the creator has the right to economic rights to his creation, where in Article 9 the creator has the right to prohibit other people from doubling the work in all its forms without permission for commercial use. This study aims to determine whether the act of publishing pieces of cinema scenes through the Instagram Stories application is categorized as copyright infringement on the film as well as knowing the form of Copyright legal protection for Widescreen Films published through social media without permission. This study uses empirical research. The location of the study was conducted at the Regional Office of the Ministry of Law and Human Rights of South Sulawesi and Cinema XXI of Makassar City. The results of the study indicate that recording movies in theaters uploaded through Instagram Stories can be categorized as violating the moral rights of the creator in terms of attribution rights if the uploader negates the identity in the video displayed. However, in terms of economic rights, copyright infringement is not found, this is because the motives used by the recording actors do not fulfill the element of seeking commercial profit. Legal protection regarding recording in theaters uploaded through Instagram Stories is regulated in Law Number 28 of 2014 concerning Copyright in Article 9 paragraph (1) letter b and in paragraph (2). Legal actions given by the cinema to the audience who perform the recording action, in the form of reprimand until the confiscation of the cellphone belonging to the audience and the making of a statement letter. But until now there have been no cases that have reached the Regional Office of the Ministry of Law and Human Rights of South Sulawesi.